IMPLEMENTASI DIGITALISASI E-PROCUREMENT DALAM MENINGKATKAN EFISIENSI, TRANSPARANSI, DAN AKUNTABILITAS PENGADAAN BARANG DAN JASA: STUDI PADA PT PLN NUSANTARA POWER UP PAITON - Ledi Diana Agustin; Moh. Fakhri Siddiqi (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2026)
This study aims to analyze the implementation of e-procurement digitalization on the efficiency, transparency, and accountability of goods and services procurement at PT PLN Nusantara Power UP Paiton. The development of digital technology encourages companies to implement electronic-based procurement systems to improve the quality of corporate governance. This study uses a qualitative descriptive method with a field research approach. Data collection techniques are carried out through observation, interviews, and documentation of parties involved in the goods and services procurement process. The results show that the implementation of e-procurement digitalization can improve the efficiency of procurement time and costs, strengthen transparency in the tender information process, and improve accountability through systematically documented data recording. In addition, the implementation of the digital system also helps minimize the potential for administrative errors and irregularities in the procurement process. However, several obstacles are still found such as limited human resources, system disruptions, and suboptimal technology integration at all stages of procurement. This study concludes that the implementation of e-procurement digitalization has a positive contribution to the governance of goods and services procurement at PT PLN Nusantara Power UP Paiton. Therefore, it is necessary to increase human resource capacity and develop a more optimal digital system so that e-procurement implementation can run optimally.